Qualitative Traits Characterization of Yoruba and Fulani Ecotype Indigenous Chickens in Derived Savannah Zone of Nigeria - Ige , A.O.; Salako, A.E.; Yakubu, A.; Adeyemi, S.A. (International Journal of Poultry Science, 2012)
Qualitative traits characteristics of indigenous Chickens in derived savannah Zone of Nigeria were studied. A total of two thousand and forty one (2,041) indigenous chickens comprising 1274 Yoruba Ecotype Chickens (YEC) and 767 Fulani Ecotype Chickens (FEC) were sampled for the study. Traits studied included Sex, Comb Size, Wattle Size, Comb Type, Ear lobe Colour, Feather Structure, Plumage and Comb Colour. The result indicated that female chickens dominated the two Ecotypes with 52.04% in YEC and 52.28% in FEC. Highest percentage of Large Comb Size was observed for male chicken in both ecotypes: 67.57% in YEC and 71.32% in FEC. Three types of wattle size were observed in the two populations (Small, Medium and Large). Proportion of Large Wattle size favoured male chickens (YEC: 51.13%, FEC: 49.38%) in both populations. Three different types of comb (Single, Rose and Pea) with Single Comb type dominant over others (94.29% in YEC and 80.44% in FEC). Three colour patterns of ear lobe were observed in YEC with White Ear Lobe (69.07%) dominated the population while five colour patterns were observed in FEC with Red Ear lobe (74.97%) dominated. Three feather structure (Normal, Frizzled and Naked Neck) pattern were observed in the two populations, Normal type had the highest percentage (YEC: 83.99%, FEC: 83.05%). Plumage colour varied widely, six different types were observed in YEC and mixed colour had the highest percentage (31.4%) followed by dominant black (25.69%) while Eight different types of plumage colour were observed in FEC in which black colour (31.55%) had the highest percentage. The study revealed a wide variation in some of the traits, therefore future study can be concentrated on selection for qualitative traits of interest.